Bibliometric Analysis of the Development of Research on Transformational Leadership in Social Organizations - Fauzan, Muhammad; Tjahjono, Heru Kurnianto; Handayani, Siti Dyah (Journal of Economics and Management Scienties, 2025)
This study aims to map publication trends, key themes, and the evolution of TL research referring to the chronological and thematic development of transformational leadership studies over time while integrating findings with relevant leadership theories. This research employs a bibliometric analysis of 92 publications indexed in Scopus (2020–2024). The keyword “transformational leadership” in the context of social organizations was mapped based on thematic clusters and annual evolution. The findings reveal a shift in TL research focus from classical themes such as job satisfaction and organizational commitment (2020–2021) toward contemporary topics such as innovation, knowledge sharing, organizational identification, and digital transformation (2023–2024). Keywords such as trust, employee engagement, and organizational performance dominate and act as mediators of organizational outcomes. Influential articles, including meta-analyses of TL and ethical leadership, studies on the mediating role of trust, knowledge management, and corporate social responsibility, strengthen the evidence of TL as a catalyst for trust, ethics, and social innovation. Cross-country analysis highlights that Pakistan, India, and Indonesia emphasize digital readiness, whereas the UK and Australia focus on psychological safety and burnout prevention.